Potential and Application of Vegetable Tanning Materials from Industrial Forest Plantation in Indonesia - Sri Mutiar; Anwar Kasim (Green Engineering Society, 2023)
Vegetable tanning materials are sourced from plants that contain tannin compounds. Tannins are obtained through the extraction method from the roots, stems, bark, or fruit of the original plant. There are several forest management companies in Indonesia that produce wood from plant species Acacia auriculiformis and Acacia mangium. Both species are known as Acacia. Acacia is an important source of tannin for material tanner vegetables. This wood is produced as a raw material for the pulp and paper industry. However, the bark contains tannin and has not been used optimally. Therefore, the study's potential and possible applications as vegetable tanning agents have been carried out. The research was started by investigating the availability of bark and extracting tannins to obtain extracts containing tannins. Furthermore, the extract obtained was applied as a vegetable tanning agent for the goatskin tanning process. The results showed that the bark of the Plant Industry Forest has the potential to be developed as a source of tannins for material vegetable tanning agents. The application of acacia bark extract in goatskin tanning has obtained tanned leather that meets the Indonesian National Standard.